2018
DOI: 10.1038/s41467-018-06066-8
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4K20 methylation mediated chromatin compaction threshold ensures genome integrity by limiting DNA replication licensing

Abstract: The decompaction and re-establishment of chromatin organization immediately after mitosis is essential for genome regulation. Mechanisms underlying chromatin structure control in daughter cells are not fully understood. Here we show that a chromatin compaction threshold in cells exiting mitosis ensures genome integrity by limiting replication licensing in G1 phase. Upon mitotic exit, chromatin relaxation is controlled by SET8-dependent methylation of histone H4 on lysine 20. In the absence of either SET8 or H4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 65 publications
(68 reference statements)
5
91
0
2
Order By: Relevance
“…We show that H4K20me3 is present in a subset of non-genic late replicating initiation zones, which are enriched in ORC/ MCM binding. This confirms our previous finding that H4K20me3-mediated ORC-DNA binding enhances origin activity in certain environments 18, 32 . Finally, we find that the global density of ORC highly correlates with replication timing, an effect observed less prominently for MCM.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We show that H4K20me3 is present in a subset of non-genic late replicating initiation zones, which are enriched in ORC/ MCM binding. This confirms our previous finding that H4K20me3-mediated ORC-DNA binding enhances origin activity in certain environments 18, 32 . Finally, we find that the global density of ORC highly correlates with replication timing, an effect observed less prominently for MCM.…”
supporting
confidence: 92%
“…H4K20 methylation has multiple functions in ensuring genome integrity, such as DNA replication 39, 45, 46 , DNA damage repair, and chromatin compaction 32, 47, 48 suggesting that the different functions are context dependent and executed with different players. We previously demonstrated that H4K20me3 provides a platform to enhance origin formation in late replicating heterochromatin 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few DNA breaks are generally sufficient to activate P53 functions 32,33 . Since the first impact of loss of SETD8 activity is excessive chromatin relaxation and progressive DNA damage after exit of mitosis 34 , we propose that the activation of p53 we detect in MM cells upon SETD8 inhibition is mainly triggered by cellular stresses during G1 progression. This would also explain why UNC0379mediated SETD8 inhibition is very toxic in P53-deficient MM cells, where the absence of a functional p53-mediated G1 arrest allows damaged cells to pursue into S-phase and accumulate a deadly level of DNA breaks, likely caused by improper replication fork progression 24 .…”
Section: Pharmacological Inhibition Of Setd8 Synergizes With Melphalamentioning
confidence: 86%
“…In a single-celled eukaryotic microbe like yeast, such a genome-scale effect could impinge on organismal fitness by reducing cell proliferation rates and/or genome stability, as delayed replication is associated with enhanced mutation frequency (45; 46). However, in mammalian cells, SirT1, the human ortholog of yeast Sir2, as well as Set8-mediated chromatin compaction limit origin function and promote genome stability (47; 48; 49). Notably, the Set-8 mechanism works at the level of limiting MCM binding to chromatin.…”
Section: Discussionmentioning
confidence: 99%